Sistema de extracción de aguas residuales por el método de vacío, para la gestión de residuos - Gualli Contreras, Andrea Abigail (2023)
One of the persistent territorial problems in different sectors of the country, due to the lack of public policies for wastewater management. In many cases, this has led to the collapse of the existing sewerage system, either due to lack of maintenance or misuse by users. Therefore, it is necessary to modernize wastewater collection, so that waste management can be effective and sustainable over time, even in areas where the gravity system is not feasible. Because of this problem, the vacuum sewerage method is proposed as an economically viable and sustainable alternative. The scope of this research of correlational type, based on the hypothesis proposed, the variables are related. Therefore, once the information is collected, the concepts are systematically categorized and the results are extrapolated. Thus, the results were obtained in terms of the projection of referential costs of the vacuum system, operation and guidelines to be considered for its implementation in the country.